The prevalence and risk factors of asthma and allergic diseases among working adolescents - (:unkn) unknown (ALLERGY IMMUNOL SOC THAILAND, 2010)
Certain occupational groups are known to be at particularly high risk of developing allergic diseases. The objective of the present study was to evaluate the prevalence of allergic diseases among working adolescents. The International Study of Asthma and Allergies in Childhood questionnaire was used. Four hundred and thirty six adolescents working in motor, lathe-finish, coiffure and textile and 366 high school students as control group were enrolled to the study. Mean age was 16.8 +/- 1.2 years and 82.9% of them were male. There was no significant difference among groups for ever and current wheezing while doctor diagnosed asthma was higher in lathe- finish group (p = 0.036). Family history of allergy, history of allergic rhinitis, and active smoking were found to be risk factors for asthma and related symptoms. Working in coiffure (p = 0.054), and textile (p = 0.003) were significant risk factors for ever allergic rhinitis. Working in lathe finish (p = 0.023), coiffure (p = .002), and textile (p < 0.001) were associated with a higher risk for current allergic rhinitis. Working in coiffure was a risk factor for ever eczema (p = 0.008) and doctor diagnosed eczema (p = 0.014). It was concluded that working in lathe-finish was associated with doctor diagnosed asthma and active smoking was a risk factor for asthma and related symptoms. Working in coiffure, textile and lathe-finish were risk factors for rhinitis, and working in coiffure was a risk factor for eczema. Preventive measures should be taken at the onset of employment in order to prevent or reduce the detrimental effects of exposures in these occupational groups. (Asian Pac J Allergy Immuno 2010;28:122-9)
Keywords: Asthma; adolescent; rhinitis; eczema; occupation; RESPIRATORY SYMPTOMS; CHILDHOOD ISAAC; RHINITIS; EXPOSURE; SMOKING; RESPONSIVENESS; SKIN